Microwave-Assisted Chemical Purification and Ultrasonication for Extraction of Nano-Fibrillated Cellulose from Potato Peel Waste - Mohsen Sadeghi-Shapourabadi; Said Elkoun; Mathieu Robert (Macromol, 2023)
Nanofibrillated cellulose was extracted from potato peel waste using a fast and green method with a simple process. To extract cellulose and eliminate non-cellulosic constituents, alkaline and hydrogen peroxide treatments were performed under microwave irradiation. The nanofibrillated cellulose was extracted from purified cellulose via TEMPO oxidation followed by ultrasonication. The TEM, FTIR, XRD, and TGA experiments were used to evaluate the structural, crystalline, and thermal properties of cellulose fiber and nanofiber. The chemical and FTIR analysis of bleached fibers indicates that almost all non-cellulosic components of biomass have been eliminated. The diameter of the extracted nanofibers is in the range of 4 to 22 nm. In terms of crystallinity, extracted nanocellulose had 70% crystallinity, compared to 17% for unprocessed lignocellulose fibers, which makes it an excellent choice for use as a reinforcement phase in biobased composites. Thermogravimetric analysis reveals that cellulose nanofibers are less thermally stable than potato peel pure cellulose, but it has a higher char content (28%) than pure cellulose (6%), which signifies that the carboxylate functionality acts as a flame retardant. The comparison between cellulose derived from microwave and conventional extraction methods confirmed that their impact on the removal of non-cellulosic materials is nearly identical.